Improvement of Technology of Cholera Toxin B-Subunit Production - A. V. Komissarov; S. A. Eremin; O. A. Volokh; O. V. Gromova; Yu. A. Aleshina; E. M. Kuznetsova; N. G. Avdeeva; L. F. Livanova; A. K. Nikiforov (Проблемы особо опасных инфекций, 2015)
Consideration is given to implementation of state-of-the-art filtration technologies for up-scaled manufacturing of cholera toxin B-subunit, produced by recombinant Vibrio cholerae non O1 KM93 strain. Selected are micro- and ultra-filtration membranes to be incorporated into manufacturing method. Investigated are the properties of cholera toxin B-subunit, obtained applying the pilot technology. The engineered method for up-scaled manufacturing of cholera toxin B-subunit makes the procedure easier-to-maintain due to tangential micro- and ultra-filtration, performed at the stage of purification and concentration. It excludes labor-consuming chromatographic purification, while retaining B-subunit properties. The studies undertaken make it possible to manufacture cholera toxin B-subunit with the same characteristics as in the case of the pilot technology, but under production conditions, and use it as a component for chemical cholera vaccine.